A novel locus on 19q13 associated with autosomal-dominant macular dystrophy in a large Greek family. Issue 12 (1st December 2006) - Yang, Z; Kitsos, G; Tong, Z; Payne, M; Gorezis, S; Psilas, K; Grigoriadou, M; Zhao, Y; Kamaya, S; Aperis, G; Petersen, M B; Zhang, K
Abstract : Objective: To describe the clinical features of and genetic locus associated with autosomal-dominant macular dystrophy (MCDR5) in a large Greek family. Methods: 26 members of a single family underwent clinical examinations and venepuncture. A genomewide linkage scan using 400 microsatellite markers distributed with an average spacing of 10 cM throughout the human genome. Results: 14 members of the study family exhibited clinical features of the disease including decreased central vision and macular abnormalities in the posterior pole of the retina. Analysis of loci known to be associated with macular dystrophy did not show positive linkage. A genomewide linkage scan showed linkage to chromosome 19q, with a two-point maximum LOD score of 5.809 at θ = 0 between the disease and marker locus D19S412. On the basis of recombination events, the disease interval was localised between markers D19S420 and D19S540 on chromosome 19q, at a span of about 3.8 cM, in an area known to contain 120 known genes/transcripts. Eleven of these genes/transcripts were sequenced, and no disease-causing mutation was identified. Conclusions: This study describes a new locus on 19q associated with autosomal-dominant macular dystrophy, designated as MCDR5. Additional study of other family members will be necessary to further narrow the interval and identify the responsible gene. The study of MCDR5 will aid in elucidation of the underlying pathogenic mechanisms for this and other macular diseases, including age-related macular degeneration.